Potassium Channel Protein KCNK6 Promotes Breast Cancer Cell Proliferation, Invasion, and Migration - Hou, Xiangchan; Tang, Le; Li, Xiayu; Xiong, Fang; Mo, Yongzhen; Jiang, Xianjie; Deng, Xiangying; Peng, Miao; Wu, Pan; Zhao, Mengyao; Ouyang, Jiawei; Shi, Lei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Breast cancer is the most common malignant tumor in women, and its incidence is increasing each year. To effectively treat breast cancer, it is important to identify genes involved in the occurrence and development of breast cancer and use them as potential drug therapy targets. Here, we found that potassium channel subfamily K member 6 (KCNK6) is significantly overexpressed in breast cancer, but its function in tumors has not been reported. We further verified that KCNK6 expression is upregulated in breast cancer biopsies. KCNK6 knockdown could inhibit the proliferation, invasion, and migration ability of breast cancer cells. This inhibitive effect may occur by weakening cell adhesion and reducing cell hardness, thus affecting the malignant phenotype of breast cancer cells. Our study confirmed for the first time that increased KCNK6 expression in breast cancer may promote breast cancer cell proliferation, invasion, and migration. Ion channels are therapeutic targets for many small molecular drugs in clinical treatment. Therefore, this paper suggests that targeting KCNK6 is of great value in breast cancer treatment, and provides a theoretical basis for KCNK6 to become a potential molecular target for breast cancer treatment in the future.